Analys av prostaglandin F2α -metabolit i blodet - Berggren Törmä, Karin (2008)
Pyometra (chronic purulent uterine inflammation) is a common disease in middle-aged and older intact bitches. The disease most frequently occurs in metoestrus and previous research studies have shown that both hormones and bacteria are involved in the development of the disease.